2011
DOI: 10.1007/s11883-011-0209-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nitrates, Nitrites, and Cardiovascular Disease

Abstract: Dietary nitrate (NO(3)), nitrite (NO(2)), and arginine can serve as sources for production of NO(x) (a diverse group of metabolites including nitric oxide, nitrosothiols, and nitroalkenes) via ultraviolet light exposure to skin, mammalian nitrate/nitrite reductases in tissues, and nitric oxide synthase enzymes, respectively. NO(x) are responsible for the hypotensive, antiplatelet, and cytoprotective effects of dietary nitrates and nitrites. Current regulatory limits on nitrate intakes, based on concerns regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 52 publications
(70 reference statements)
1
47
1
Order By: Relevance
“…The results are, however, inconsistent with respect to CVD -recent review articles highlighted that total dietary nitrite and nitrate may have cardiovascular protective properties [18] by lowering blood pressure and by having antiplatelet and cytoprotective effects [19]. In contrast, some studies indicated that high concentration of nitrites in diet is related to endothelial dysfunction and impaired insulin response in adults [20].…”
Section: Discussionmentioning
confidence: 99%
“…The results are, however, inconsistent with respect to CVD -recent review articles highlighted that total dietary nitrite and nitrate may have cardiovascular protective properties [18] by lowering blood pressure and by having antiplatelet and cytoprotective effects [19]. In contrast, some studies indicated that high concentration of nitrites in diet is related to endothelial dysfunction and impaired insulin response in adults [20].…”
Section: Discussionmentioning
confidence: 99%
“…Even though 80% of the basal plasma nitrite levels derive from the oxidation of NO [28], reduction of nitrate also significantly contributes to increasing nitrite levels and, eventually, to the synthesis of NO [29,30] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrites are frequently used in the preservation of processed meat (cured meats) and have been suggested to affect the risk of HF, but results are inconsistent-recent review articles highlighted that total dietary nitrite and nitrate may have cardiovascular protective properties 16 by hypotensive, antiplatelet, and cytoprotective effects. 17 In contrast, some studies indicated that high concentration of nitrites in diet is related to endothelial dysfunction and impaired insulin response in adults.…”
mentioning
confidence: 99%
“…Nitrites are frequently used in the preservation of processed meat (cured meats) and have been suggested to affect the risk of HF, but results are inconsistent-recent review articles highlighted that total dietary nitrite and nitrate may have cardiovascular protective properties 16 by hypotensive, antiplatelet, and cytoprotective effects. 17 In contrast, some studies indicated that high concentration of nitrites in diet is related to endothelial dysfunction and impaired insulin response in adults.18 Phosphate-containing food additives can promote HF by impairment of the calcium phosphate metabolism. Among coronary heart disease patients, higher levels of serum phosphate were associated with increased risk of new HF and coronary heart disease events compared with participants with lower levels.…”
mentioning
confidence: 99%